NEW FRAGMENTS OF GILGAMEŠ AND OTHER LITERARY TEXTS FROM KUYUNJIK. (17th March 2015) - Jiménez, E.
Abstract : The public availability of photographs of the entire British Museum Kuyunjik collection has allowed the identification of many hitherto unplaced fragments. Some of them are particularly relevant for the reconstruction of passages in a number of ancient Mesopotamian literary texts. These are published here for the first time. They include three new fragments of the Gilgameš epic, one or two of the Theodicy, several of the Diviner's Manual and of the Rituals of the Diviner, several prayers previously only poorly known, and fragments from the seventh tablet of the exorcistic series Muššuʾu .